Suprasegmental Phonology and Segmental Form : Segmental Variation in the English of Dutch Speakers. - James, Allan R. (Linguistische Arbeiten., 1986)
Suprasegmental Phonology and Segmental Form: Segmental Variation in the English of Dutch Speakers.